Large scale distribution of dioxins, PCBs, heavy metals, PAH-metabolites and radionuclides in cod (Gadus morhua) from the North Atlantic and its adjacent seas. (April 2016) - Karl, Horst; Kammann, Ulrike; Aust, Marc-Oliver; Manthey-Karl, Monika; Lüth, Anja; Kanisch, Günter
Abstract: Regarding cod as sea food for human consumption and as bio indicator of the marine eco system, this study is the first approach to combine the analysis of organic and inorganic contaminants and radionuclides in cod muscle as well as PCDD/Fs and dl-PCBs in its livers from the same fishing areas. Concentrations of 1-hydroxypyrene, PCDD/Fs, PCBs, cesium-137 (Cs-137), cadmium and lead were determined in individual or pooled samples over a wide geographic area, including Greenland Seas, Barents Sea, North and Baltic Sea. Highest concentrations were found in samples from the Baltic Sea, lowest in the pristine areas of the Barents Sea and Greenland. Levels of contaminants in cod muscle were found to be far below the established EU maximum levels (ML), regardless of which fishing grounds. In contrast to this, most cod liver samples from the North and Baltic Sea showed PCDD/F and PCB contents exceeding the ML. In addition, new background assessment criteria (BAC) for 1-hydroxypyrene in cod of 4.6 ng mL −1 bile and for Cs-137 a BAC of 0.16 Bq kg −1 wet weight are proposed to be included in the European Marine Strategy Framework Directive for cod from the Northeast Atlantic. Graphical abstract: Highlights: Levels of contaminants in cod provided for human consumption purposes and as bio indicator for the eco system are discussed. Concentrations of organic contaminants and Cs-137 in cod decreased gradually from the Baltic Sea to Greenland depending on the fishing area. Very low concentrations of all contaminants were found around Greenland and the Barents Sea. New background concentrations in cod are proposed for 1–hydroxypyrene and Cs-137.